Do Elite Universities Overpay Their Faculty? - Garro-Marín, César; Kahn, Shulamit; Lang, Kevin (The Review of Economics and Statistics, 2026)
Abstract No. Elite institutions offer high salaries because they hire the most valued faculty. Moreover, in contrast to the broader labor market, faculty are equally likely to move up and down the prestige ladder, and they increase their salary either way. We speculate that these facts reflect the visible nature of faculty productivity and the sporadic nature of academic job openings.